2000
DOI: 10.1101/gad.819500
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetics of prostate cancer

Abstract: Prostate cancer afflicts one man in nine over the age of 65 and represents the most frequently diagnosed cancer in American men (Coffey 1993). Early detection through serum testing for prostate specific antigen (PSA) and improved procedures for surgical intervention and radiation therapy have significantly reduced the number of fatalities; however, there is still no effective cure for men with advanced disease. Therefore, much research has been dedicated to identifying prognostic markers that distinguish indol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
527
0
10

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(543 citation statements)
references
References 225 publications
(260 reference statements)
6
527
0
10
Order By: Relevance
“…Only 1 of 8 samples (N1) of normal prostate (surgically removed because of bladder carcinoma) grew in culture, whereas we successfully derived two cell strains from benign prostatic hyperplasia (C10 and C17) and one from a contralateral normal tissue characterized by the presence of prostate intraepithelial neoplasia (C16sx). Cultures from normal/hyperplastic tissue (N1, C10, C17, and C16sx) and cancer had similar growth rate (10,11). Importantly, all cultures had limited life span (20-25 population doublings) and similar cell morphology, as described (12).…”
Section: Isolation Of Prostate Epithelial Culturesmentioning
confidence: 95%
“…Only 1 of 8 samples (N1) of normal prostate (surgically removed because of bladder carcinoma) grew in culture, whereas we successfully derived two cell strains from benign prostatic hyperplasia (C10 and C17) and one from a contralateral normal tissue characterized by the presence of prostate intraepithelial neoplasia (C16sx). Cultures from normal/hyperplastic tissue (N1, C10, C17, and C16sx) and cancer had similar growth rate (10,11). Importantly, all cultures had limited life span (20-25 population doublings) and similar cell morphology, as described (12).…”
Section: Isolation Of Prostate Epithelial Culturesmentioning
confidence: 95%
“…The etiologic agents that contribute to the development of human prostatic diseases such as benign prostate hyperplasia (BPH) and prostate cancer remain largely unknown (1)(2)(3)(4). Studies have suggested close links among certain infections of the prostate, chronic inflammation, and the development of inflammation-associated prostatic diseases (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…There is an urgent need for appropriate diagnostic and prognostic markers, in addition to the established serum protease prostate-specific antigen (PSA), allowing an early diagnosis and the prediction of the clinical behavior of individual tumors. Although the involvement of certain genes and of chromosomal aberrations in prostate carcinogenesis has been suggested (2,3), the molecular mechanisms underlying the initiation and progression of prostate cancer are only poorly understood.…”
mentioning
confidence: 99%